Features of the Technology Companies’ Development in the Context of the Introduction of Financial Technologies: Strategic Trends and OTSW-analysis - A. K. Yakovleva (Управленческое консультирование)
The article reveals the content of the concept of “financial technology”, emphasizes its importance in the strategic development of technology companies in the financial sector. It reflects the features of financial technologies and services as tools to stimulate innovation in the financial sector. The research methodology is based on taking into account the dependence of the transition to the creation and improvement of technological companies in the banking sector on progress in financial technologies. The analysis of the development strategy of Russian technology companies with a banking license was carried out by reviewing the initial stages of its development (according to the methodology of V.L. Kvint). The results of the trends and patterns’ analysis, as well as the OTSW-analysis of the technology companies’ development in Russia in the context of the financial technologies’ introduction are presented. Based on the materials of the study, we can conclude that the further formation of the financial sector largely depends on financial technologies that affect the process of digital transformation, increasing the openness of financial services. However, these processes create new and complicate the old challenges. In the domestic market, avant-garde financial companies launch and promote transformational strategies, create ecosystems around themselves, turning into technology companies. The main factor in such business models’ changes in the companies is the strategic potential inherent in these actions and the possibility of providing competitive advantages for the company in the future due to upcoming technological changes (including changes in the technological order). At the end of the work strategic recommendations were formulated to create and improve an enabling environment for the financial technologies’ development.